Nasal Symptoms of Chronic Rhinosinusitis were Related to Its Nasoendoscopic Findings: A Retrospective Cohort Study at Dr. Soetomo General Academic Hospital, Surabaya - Chandra, Christopher Marcellino; Kristyono, Irwan; Soegiarto, Gatot; Nugroho, Puguh Setyo (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2024)
Highlights: Nasal congestion was the most common symptom presented in CRS patients. Nasal symptoms of CRS were positively associated with nasoendoscopic findings (Polyp, Edema, Secretions).   Abstract Introduction: Chronic rhinosinusitis (CRS) is often encountered in Indonesia. Nasal endoscopy, or nasendoscopy, is considered the gold standard for assessing the severity of CRS. However, as nasendoscopy is unavailable in Indonesia, only symptom assessments can be conducted at primary healthcare facilities. This study aimed to elucidate the relationship between nasoendoscopic findings based on the Lund-Kennedy score (LKS) and symptoms in CRS patients based on the visual analogue scale (VAS) score. Methods: This retrospective analytic study evaluated CRS cases identified in the Ear, Nose, and Throat (ENT) Outpatient Clinic of Dr. Soetomo General Academic Hospital, Surabaya, from July 2021 to July 2022.  Statistical analysis was conducted using Spearman’s rank correlation test to identify the correlation (r) between LKS and the VAS score. Statistical significance was achieved if p<0.05. All statistical tests were conducted using the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 26.0 for Windows. Results: A total of 57 CRS patients were included in this study, mostly females (64.9%) and those aged 50–59 years old (26.9%). Nasal congestion was the dominant nasal symptom (80.7%), with mostly moderate symptom severity (VAS 4-7) reported. Across both nasal cavities, the most frequent nasoendoscopic finding among CRS patients was nasal edema (82.4% and 93%). A positive and weak correlation existed between the total VAS score of all symptoms and the total LKS of both nasal cavities (r=0.387, p=0.003). Conclusion: The nasal symptoms of CRS patients were significantly associated with its nasoendoscopic findings (Polyp, Edema, Secretions).